Let us say there are x number of candies .
For first student,
He ate 3/20 of all candies, so 3/20 (x)
He also ate 1.2 lb of candies.
Total candies first student ate = (3/20) x +1.2
Second student ate 3/5 of all candies that is (3/5)x
He also ate 0.3 lb of candies.
Total candies second student ate = (3/5)x +0.3
Since total candies for both will be same, so equating the two expressions
![\frac{3}{20} (x) +1.2 = \frac{3}{5} x +0.3](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B20%7D%20%28x%29%20%2B1.2%20%3D%20%5Cfrac%7B3%7D%7B5%7D%20x%20%2B0.3%20%20)
x=2
So there are 2 lb of candies in total.
First student ate = 0.3 +1.2 = 1.5lb of candies.
Second student ate = 1.5 lb of candies